Eliminating the Interference of Oxygen for Sensing Hydrogen Peroxide with the Polyaniline Modified Electrode - Gu, Yesong (Molecular Diversity Preservation International (MDPI), 2008)
Polyaniline (PANI) has been shown to possess excellent catalytic activity toward oxygen reduction, however, this molecule may interfere with the electrochemical measurement of other targets when using a polyaniline modified platinum (PANI/Pt) electrode. In this study, we have demonstrated the considerable effects of dissolved oxygen on the sensing of hydrogen peroxide with the PANI/Pt electrode. Accordingly, we proposed a strategy to eliminate the influence of dissolved oxygen with oxygen scavengers. Our results indicated that as an oxygen scavenger sodium thiosulfate was very effective in the removal of dissolved oxygen from the sample solution, and had negligible effect on the quantification of hydrogen peroxide when its applied concentration was below 1 mM.